the potential of face-to-face education and virtual education - Riofrío Guadalupe, Ligia del Pilar; Arroba Bermeo , Milton Ernesto; Arroba Bermeo, Ítalo Rosendo (SATHIRI, 2022)
The objective of this work is to analyze the potential of face-to-face education in the classroom contrasted with virtual education at home within the teaching-learning process in pandemic time and how the learning and knowledge transmission processes must be appeared. The first one through a classroom and the second online in order to know the effectiveness of both of them. Consequently, their successes, advantages, and disadvantages stand out from each one. In general, the research allowed us to interpret the importance of face-to-face and online classes in order to make criticism, objective precision and the most important to determine the position of the teacher both in face-to-face and virtual classes with different roles as well as with challenges since they must be trained and professionalized to be in line with the technological world.